Unveiling drivers of fecundity in an urban white-tailed deer population over 20 years of active management - Readyhough, TS; Cepek, JD; Shaffer, EE; Dennis, PM; Byer, NW; Hausman, CE; Montgomery, R; Moll, RJ (Springer, 2024)
White-tailed deer (Odocoileus virginianus; hereafter “deer”) are keystone herbivores that exert considerable ecosystem impacts. Quantifying drivers of urban deer demography, including fecundity (number of fetuses/doe), is paramount for understanding deer ecology and making management decisions, but this information is lacking for urban deer populations. In non-urban areas, doe age, population density, winter severity, and plant primary productivity influence fecundity. Increased forage availability in urban areas may dampen climatic effects on deer reproduction, but other threats and stressors might mitigate the positive effects of anthropogenic resources. We investigated how management, habitat, winter severity, and forage availability influenced deer pregnancy and fecundity using structural equation models using 20 years of data from a deer management program in a large urban park system. The proportion of pregnant fawns, yearlings, and adults were 0.16, 0.95, and 0.97, respectively, while fecundity (fetuses/doe) was 0.17, 1.59, and 1.88. Low fawn pregnancy rates and stable adult fecundity rates indicated a robust deer population. Age and body condition were the strongest predictors of fecundity. Unexpectedly, management, habitat (including urbanization), winter severity, and forage availability did not directly affect fecundity. Winter severity had a counterintuitive positive effect on adult deer body mass. Management affected yearling body masses: higher deer removal in the previous year was associated with increased current year removal and lower yearling body masses. Together, these results indicate that the environmental factors that commonly affect rural populations do not drive fecundity in this system, potentially reflecting unique characteristics of managed urban deer populations.